1981
DOI: 10.1093/jn/111.7.1240
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Its Metabolites in Human and Bovine Milk

Abstract: Human and bovine milk were analyzed for vitamin D, 25-hydroxyvitamin D, 24,25-dihydroxyvitamin D, 25,26-dihydroxyvitamin D and 1,25-dihydroxyvitamin D using exhaustive chromatographic purification procedures coupled with ligand binding assays. Human milk contained the following amounts of antirachitic sterols (pg/ml, mean +/- SD, n = 5): 39 +/- 9 vitamin D; 311 +/- 31 25-hydroxyvitamin D; 52 +/- 8 24,25-hydroxyvitamin D; 32 +/- 9 25,26-dihydroxyvitamin D; 5.1 +/- 0.3 1,25-dihydroxyvitamin D. Normal bovine milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
0
4

Year Published

1985
1985
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(156 citation statements)
references
References 34 publications
8
144
0
4
Order By: Relevance
“…[71][72][73][74]126 In a lactating mother supplemented with 400 IU/day of vitamin D, the vitamin D content of her milk ranges from Ͻ25 to 78 IU/L. 73,74,[126][127][128][129] Infants who are exclusively breastfed but who do not receive supplemental vitamin D or adequate sunlight exposure are at increased risk of developing vitamin D deficiency and/or rickets. 7,[10][11][12]14,18,81,130 Infants with darker pigmentation are at greater risk of vitamin D deficiency, 131 a fact explained by the greater risk of deficiency at birth 132 and the decreased vitamin D content in milk from women who themselves are deficient.…”
Section: The Effect Of Maternal Vitamin D Supplementation During Lactmentioning
confidence: 99%
“…[71][72][73][74]126 In a lactating mother supplemented with 400 IU/day of vitamin D, the vitamin D content of her milk ranges from Ͻ25 to 78 IU/L. 73,74,[126][127][128][129] Infants who are exclusively breastfed but who do not receive supplemental vitamin D or adequate sunlight exposure are at increased risk of developing vitamin D deficiency and/or rickets. 7,[10][11][12]14,18,81,130 Infants with darker pigmentation are at greater risk of vitamin D deficiency, 131 a fact explained by the greater risk of deficiency at birth 132 and the decreased vitamin D content in milk from women who themselves are deficient.…”
Section: The Effect Of Maternal Vitamin D Supplementation During Lactmentioning
confidence: 99%
“…Breast milk is indisputably the ideal food for infants; however, breast milk typically contains about 25 IU/L which is insufficient for rickets prevention. 15,16 Although there is evidence that limited sun exposure may prevent rickets in some breast-fed infants concerns over the health risk of sun exposure had led to the recommendation that all breast-fed infants receive supplemental vitamin D. 17,18 Thacher et al reported that children with rickets had a greater proportion of first degree relatives with a history of rickets. 19 A similar diet and environment may be the reason for rickets in families.…”
Section: Discussionmentioning
confidence: 99%
“…In most infants, Vitamin D stores acquired from the mother are depleted by approximately 8 weeks of age [43]. Human milk contains a very low concentration of Vitamin D (approximately 20 -60 IU/L), which represents 1.5% -3% of the maternal level [44]. This low concentration is not sufficient to maintain an optimal Vitamin D level in the newborns if exposure to sunlight is limited.…”
Section: The Significance Of Vitamin D In Lactationmentioning
confidence: 99%